Teoria dos números: uma introdução motivadora direcionada aos docentes do ensino básico - Faria, Alexandre Augusto Cavalcante de (2015)
Facing the mathematics teacher of basic education, this paper presents extensive motivating material in Number Theory, area of Pure Mathematics branch that studies the integers as well as a widw class of problems arising from this study. Topics covered are finite principle of induction, divisibility, greatest common divisor, primes and modular congruence. The theory is discussed in an understandable, balanced in its formalism, always preceded by motivating examples and with a reasonable amount of exercise resolved, the classics to the Olympic level. Historical notes are also included as a motivational element. We also present suggestions for activities that can be applied to the student. What is expected, with everything, is to help the teacher in their performance in the classroom, by understanding the basic topics of number theory; urging him to now Olympic form groups of intensive training, and make them aware of the importance of their continuing education and thereby encourage, your enrollment in any master's program.